2015
DOI: 10.5897/ajfs2014.1250
|View full text |Cite
|
Sign up to set email alerts
|

Influence of smoking method on quality of traditional smoked Bonga shad (Ethmalosa frimbriata) fish from Lagos State, Nigeria

Abstract: This study was carried out to assess the influence of smoking method on quality attributes of traditional smoked bonga shad fish. Fresh bonga shad fish (100 samples) and smoked bonga shad fish (100 samples) were collected from 20 different processing centres and the fresh samples were smoked with convectional smoking kiln as the control. Laboratory analyses were conducted and each batch was assessed for; proximate and quality analyses. The results obtained show significant variations (p<0.05) for all the proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 7 publications
3
12
1
Order By: Relevance
“…The PV of all smoked herring increased significantly ( p < .05) throughout processing and unbleached smoked herring compared to bleached smoked herring had the higher PV (30.12 meq O 2 /kg of oil). The increases of PV in smoked herring are in agreement with the finding of Adeyeye, Oyewole, Obadina, and Omemu () when study the effect smoking process on lipid quality of Bonga shad ( Ethmalosa frimbriata ) fish from Lagos State in Nigeria. These finding are also in accordance with the results obtained by Beltran and Moral () on hot smoking sardine fillets, which noted the oxidation of PUFAs present in fish oil.…”
Section: Resultssupporting
confidence: 89%
“…The PV of all smoked herring increased significantly ( p < .05) throughout processing and unbleached smoked herring compared to bleached smoked herring had the higher PV (30.12 meq O 2 /kg of oil). The increases of PV in smoked herring are in agreement with the finding of Adeyeye, Oyewole, Obadina, and Omemu () when study the effect smoking process on lipid quality of Bonga shad ( Ethmalosa frimbriata ) fish from Lagos State in Nigeria. These finding are also in accordance with the results obtained by Beltran and Moral () on hot smoking sardine fillets, which noted the oxidation of PUFAs present in fish oil.…”
Section: Resultssupporting
confidence: 89%
“…The values were almost doubled compared to the fat content of fresh tilapia fillet (4.25%). This result is inaccordance with study conducted by Adeyeye et al (2015), that showed a significant increase in fat content of the Bonga shad fillets after smoking process, from 6.46%-20.84% in fresh fillets to 16.13%-20.84% in smoked fillets. This was possibly due to the biochemical reactions occured during smoking which might increase the fatty acid content of the fillets (Dhanapal et al, 2012) as well as the addition of olive oil into the fillets in the experiment.…”
Section: Proximate Composition Of Smoked Tilapia Filletssupporting
confidence: 52%
“…The denaturated protein will be coagulated when further heated at temperature of 50 o C or higher (Ghozali, Muchtadi, & Yaroh, 2004). However, other studies showed an opposite results (Gall, Otwell, Koburger, & Appledorf, 1983;Gokoglu, Yerlikaya, & Cengiz, 2004;Adeyeye et al 2015) which reported that the fillets experienced heat process had a higher protein contents compared to the raw fillets.…”
Section: Proximate Composition Of Smoked Tilapia Filletsmentioning
confidence: 92%
“…Indeed, fish consumption is associated with reduction of death from coronary heart disease and reduction of colorectal cancer (Aglago et al, 2020;Clifton & Keogh, 2017). Although several studies were carried out on smoked fish and smoked-dried fish (Adeyeye, Oyewole, Obadina, & Omemu, 2015;Amos & Paulina, 2017;Anihouvi et al, 2019;Assogba et al, 2019;Olayemi, Raji, & Adedayo, 2012), to our best knowledge, none of them provided relevant information on the quality of some of their nutrients, mostly the fatty acids, and their contribution to nutrients intake in the Beninese context. This study aims to assess the consumption of smoked fish and smoked-dried fish produced in South Benin and to estimate the protein, lipid, and fatty acid daily intakes for adult in the study area.…”
Section: Introductionmentioning
confidence: 99%